Solar Integrated System for Increasing Energy Efficiency (International Journal of Innovative Research in Engineering & Management, 2021)
Of the many hardships at present faced globally, one is how to  minimalize energy consumption by the consumption of fossil  fuels due to the adverse social & environmental influences and  worth unpredictability. Thus one of the approach is to make best  use of the renewable sources of energy such as energy of sun in  order to adhere to the global policies of clean energy  development. Our country India has raised alarms in this issue.  The combination of photovoltaic with thermal collector system  was assumed in the direction of converting simultaneously the  solar energy into electrical energy and heat energy as well. This  whole process is done to encounter the low energy obtained  when the two are used independently. Hence the concept of using the combination of thermal system  with photovoltaic was to boost and optimization of PV panel  efficiency. The construction of PV/T model uses water for  conversion to thermal energy by the use of an appropriate  technology.
Keywords: Photovoltaic PV; PV/T module Photovoltaic and thermal combined system and renewable solar energy